МЕТОДОЛОГІЧНІ ПІДХОДИ ФОРМУВАННЯ ІНФОРМАЦІЙНО-КОМУНІКАЦІЙНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНІХ ФАХІВЦІВ ДОШКІЛЬНОЇ ОСВІТИ - Semchuk, Svitlana I.; Gavriliuk, Svitlana M.; Butenko, Olga H. (Information technologies and learning tools, 2018)
The article substantiates the methodological approaches that reflect the interrelation and interconditionality of phenomena and processes of formation of the information and communication competence of future specialists in preschool education, namely: system- and activity-based, personally-oriented, integrative, environmental and competence-based. The authors have determined that the personally-oriented approach presupposes that each student must fulfill as much as possible all their individual traits in their diversity and uniqueness; the integrative approach contributes to overcoming the contradictions between the principle of unity of knowledge and its division into fundamental and special ones, as well as those between the ever-increasing amount of knowledge and the limited school time to learn it; the environmental approach promotes the creation of the informational and communication environment of a higher educational institution which influences the formation of informational and communication competence of future specialists in preschool education and is an influential factor for introducing the innovations in the educational process and gives students an opportunity to choose free the content and form of activity; the competence-based approach defines the ability of a future specialist in preschool education to apply the information and communication technologies in the educational process, use information, be flexible and adapt in a changing information space in accordance with their own needs and requirements of the modern society. It has been established that the process of formation of the information and communication competence of future specialists in preschool education is conditioned by a special organization of the teaching and educational process at a higher educational institution which ensures the unity, interrelation, consideration and development of the professional and information and communication components in future specialists in preschool education, with proper purposefulness, the relevant gradual organization and procedural and content-related support. The authors have also presented the definition of information and communication environment of a higher educational institution.